2017
DOI: 10.1007/s10103-017-2386-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of arginine A-specific cysteine proteinase gene expression profiling in clinical Porphyromonas gingivalis isolates against photokilling action of the photo-activated disinfection

Abstract: Porphyromonas gingivalis is a significant root canal pathogen capable of causing endodontic infections, which during their treatment may receive sub-lethal doses of photo-activated disinfection (sPAD). As sPAD can influence microbial virulence, this study was designed to evaluate the effect of sPAD on gene expression level of arginine A-specific cysteine proteinase (rgpA), as one of the underlying virulence factors involved in the development of endodontic infection via P. gingivalis strains. To find out the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There have been a lot of studies which have measured the efficiency of ICG-aPDT in its bactericidal aspect. [17][18][19][20][21][22][23][24][25][26][27] In an investigation by Omar et al, photo-activated ICG with light from a NIR laser was able to eradicate common burn wound pathogens. 17 In fact, this method has been estimated for different kinds of bacterial species, from periodontal pathogens to nosocomial ones, and in all of them, this method has been reported as an effective antibacterial method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a lot of studies which have measured the efficiency of ICG-aPDT in its bactericidal aspect. [17][18][19][20][21][22][23][24][25][26][27] In an investigation by Omar et al, photo-activated ICG with light from a NIR laser was able to eradicate common burn wound pathogens. 17 In fact, this method has been estimated for different kinds of bacterial species, from periodontal pathogens to nosocomial ones, and in all of them, this method has been reported as an effective antibacterial method.…”
Section: Discussionmentioning
confidence: 99%
“…17 In fact, this method has been estimated for different kinds of bacterial species, from periodontal pathogens to nosocomial ones, and in all of them, this method has been reported as an effective antibacterial method. 13,18,19 According to Boehm et al only less than 10% of Porphyromonas gingivalis could survive from ICG-aPDT, 20 or Fekrazad et al monitored the bactericidal effect of ICG-aPDT up to 96.68% on this bacterium. 21 In this way, Pourhajibagher et al suggested that the higher concentration of ICG could improve the bactericidal and anti-biofilm effect of this method (ICG-aPDT) on P. gingivalis, which led to decreasing cell survival up to 30.4% in CFU/mL and 25.1% in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of photodynamic therapy and Pg in particular have utilized lasers at 405, 532, 630–690, 805–830 and 905–980 nm and LEDs ranging from 390 to 480 and 565 to 671 nm. Among the photosensitizers examined in research involving Pg , the most extensively studied to date have been indocyanine green [ 91 , 92 , 93 ], methylene blue [ 94 , 95 , 96 ] and toluidine blue [ 97 , 98 , 99 ]. Other photosensitizers have included: aminolevulinic acid [ 100 ], azulene [ 101 ], β-NaYF 4 :Yb 3+ , Tm 3+ @TiO 2 (termed UCNPs@TiO 2 ) [ 102 ], BLC 1010 and BLC 1014 [ 103 ], cadmium telluride nanocrystals [ 104 ], captopril-protected gold clusters [ 105 ], cationic amino acid-porphyrin conjugate 4i [ 106 ], Chlorin-e6 [ 103 , 107 , 108 ], chloro-aluminum phthalocyanine [ 109 , 110 ], Coumarin 6 [ 111 ], Curcumin [ 112 , 113 ], curcumin-NP [ 114 ], cyanidin-3-glucoside [ 115 ], doxycycline [ 116 ], erythrosine [ 115 , 117 ], graphene silver polymethyl methacrylate [ 118 ], lysine-porphyrin conjugate 4i [ 119 ], meta-tetra(hydroxyphenyl)chlorin (mTHPC) [ 120 ], oxyhemoglobin-based oxyHb@IR820 [ 121 ], phenothiazine chloride [ 122 , 123 , 124 ], phloxine B [ 125 ], Photodithazine [ 126 ], phycocyanin [ 127 ], protoporphyrin I...…”
Section: Mode 5: Cell Lysis Through Drug/light Interaction (Apdt)mentioning
confidence: 99%